CONCEPTUAL BACKGROUNDS OF RADON BALNEOTHERAPY-RELATED LIVER RESTORATIVE MORPHOGENESIS IN EXPERIMENTAL AUTOIMMUNE DAMAGE - Yegorova Т.М. (World of Medicine and Biology, 2015)
The experiment was conducted on nonlinear white mature male rats. Conducted lectin histochemical study, electron microscopic, morphometric and method of statistical analysis. Experimentally proved sanogenetic efficacy of radon balneotherapy autoimmune liver damage as analogue of autoimmune hepatitis, namely - braking of lymphocytic autoagression and its consequences, and especially manifestation active of restorative morphogenesis through adaptogenic and immunomodulatory (with increased of suppressor units) properties of radon.